Application of Technical Gases and Their Families in Modern Industrial Technologies: A Review - Simonenko Iu.M.; Hrudka B.H.; Chyhrin A.A.; Kostenko Ye.V. (Problems of the Regional Energetics)
The aim of the study is to review the use of gas products of natural and synthetic origin and their future application prospects. To achieve this goal, a number of high-tech technologies were pre-sented and analysed. The phase equilibrium parameters of inert and fluorine-containing gases were shown, as well as the temperature ranges in which certain refrigerants can be applied. Ex-amples of cooler schemes for providing rectification processes at 28 and 210 K were given. The processes of refrigeration cycles in T-s diagrams of neon and R116 (hexafluoroethane) were shown. Schemes of helium systems for heat removal at the level of 5…28 K were considered. The areas of application of Xe, Kr, Ne, and He in modern technologies, particularly in laser technology, space exploration, lamp industry, and medicine, were highlighted. The most signifi-cant result of the work is the determination of the important role of isotopic components of inert gases for the future of energy, functional diagnostics, metrology, and other fields. In semicon-ductor manufacturing, many inert gases are used as protective environments and working media in ion-plasma and ion-beam etching in vacuum chambers. In plasma chemical surface treatment, substances containing one or more halogen atoms act as active gases. The significance of the results achieved is evident in that, in the context of a global shortage of technical gases, the de-velopment of resource-saving technologies is becoming relevant. Among these, gas product re-cycling, where gas concentrates were obtained from used mixtures, enriched, and subjected to deep purification for the secondary use of target products, is the most promising.